Design of a mine-used bus type optical substation - Fei DENG (Meikuang Anquan)
The coal mine safety monitoring system plays a very important role in coal mine safety production. It mainly collects sensor disaster information such as methane and carbon monoxide through monitoring substations and analyzes it in real time to achieve functions such as over limit sound and light alarm, power outage, wind power locking control, etc. Traditional monitoring substations use bus type cable transmission. Due to the widespread use of large electromechanical equipment and frequency converters, electromagnetic interference problems have become increasingly prominent in underground communication equipment in coal mines. Some electromagnetic interference has seriously affected the normal communication between monitoring substations and sensors, causing problems such as flashing, high values, slow transmission rates, long inspection cycles, short communication distances, weak anti-interference capabilities, and low levels of intelligence in monitoring substations. Due to the use of the principle of total reflection of light in fiber optic transmission, signal transmission is achieved inside the fiber optic cable, which is not affected by electromagnetic radiation interference and can fundamentally solve the problem of electromagnetic interference in long-distance cable transmission. Secondly, the transmission speed of light in optical fibers is close to the speed of light, while the transmission speed of electrical signals in cables is slower. Therefore, the transmission speed of optical signals in optical fibers is much higher than that of electrical signals in cables. In order to solve the problems of slow transmission speed and weak anti-interference ability in bus type cable monitoring substations, a design scheme for a mine-used single-mode single fiber bus type optical substation is proposed. The key technologies of the bus type optical substation, the transceiver principle of the single-mode single fiber optical module, and the application of the optical module in the substation are introduced in detail. Through various performance tests in the laboratory and combined with the actual application situation on site, the signal transmission performance and anti-interference ability between the bus type optical substation and the bus type optical sensor are tested. All indicators of the bus type optical substation are higher than those of the traditional bus type cable monitoring substation. The bus transmission rate reaches 10 Mbit/s, the transmission distance reaches 10 km, and the electromagnetic compatibility reaches level 4, fully meeting the requirements of the new generation intelligent monitoring system for monitoring substations.